Coronary Artery Aneurysmal Disease and Acute Coronary Syndrome - Wesam Ostwani MD; Holly Fleming MD; Carlos A. Roldan MD (SAGE Publishing, 2016)
The patient is a 70-year-old male with no other atherogenic risk factors who presented with an acute coronary syndrome (ACS) of unstable angina subsequently complicated by a non-ST elevation myocardial infarction (NSTEMI). The patient's presentation posed 3 unique features: (1) cardiac catheterization demonstrated nonobstructive 3-vessel multi-aneurysmal coronary artery disease with sluggish antegrade coronary flow; (2) a nonobstructive aneurysmal dissection flap based on contrast staining of the mid left anterior descending artery, which may have led to in situ nonocclusive thrombosis and distal microvascular embolization; and (3) successful conservative medical therapy of coronary artery aneurysmal disease (CAAD) complicated with ACS. CAAD has an incidence of 1.5% to 4.9% in adults. The most common etiology of CAAD is atherosclerotic coronary artery disease. There are no guidelines for the management of CAAD complicated by ACS, and controversies exist as to whether conservative, catheter-based, or surgical management should be pursued.